The Influence of Social Pressure, Market Pressure, Shareholder Pressure and The Reputation of Public Accounting Firms on Carbon Emission Disclosure - Rika Fitriyani Wardiman; Dul Muid; Hamdani Hamdani (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2023)
This study aims to examine and obtain empirical evidence regarding the effect of social pressure, market pressure, shareholder pressure, and public accounting firm’s reputation on carbon emission disclosure in non-financial companies in Indonesia. In this study, carbon emission disclosure was used as the dependent variable, while the independent variables of this study are social pressure, leverage and profitability which represent market pressure, market capitalization and ownership concentration as proxies for shareholder pressure, and then public accounting firm’s reputation.This research was conducted quantitative methods. The population in this study are non- financial companies listed on the Indonesia Stock Exchange in 2017-2019. The sample of this study was selected using purposive sampling method to obtain 39 non-financial companies that published sustainability reports and were listed consecutively on the Indonesia Stock Exchange from 2017 to 2019. Multiple regression analysis is the statistical method used to test the hypothesis in this study.The results of this study showed that social pressure have a significant effect on carbon emission disclosure. Meanwhile, market pressure with leverage and profitability proxies, then shareholder pressure represented by market capitalization and ownership concentration, and the reputation of public accounting firms doesn’t have significant effect on carbon emission disclosure.